Sudden flaccid paralysis - Tariq, Mohammad (BMJ Case Rep, 2015)
Periodic thyrotoxic paralysis is a genetic condition, rare in the West and in Caucasians. Thyrotoxicosis, especially in western hospitals, is an easily overlooked cause of sudden-onset paralysis. We present a case of a 40-year-old man who awoke one morning unable to stand. He had bilateral lower limb flaccid weakness of 0/5 with reduced reflexes and equivocal plantars; upper limbs were 3/5 with reduced tone and reflexes. ECG sinus rhythm was at a rate of 88/min. PR interval was decreased and QT interval increased. Bloods showed potassium of 1.8 mEq/L (normal range 3.5–5), free T4 of 29.2 pmol/L (normal range 6.5–17) and thyroid-stimulating hormone (TSH) of <0.01 mIU/L (normal range 0.35–4.94). Random urinary potassium was 8.8 mEq/L (normal range 12.5–62.5). The patient was admitted initially to intensive therapy unit and given intravenous potassium. His symptoms resolved within 24 h. He was diagnosed with thyrotoxic periodic paralysis. He was discharged on carbimazole and propanolol, and follow-up was arranged in the endocrinology clinic.